Obesity may impair response to ovarian stimulation. A retrospective observational study on oocyte quality - Iavarone, Irene; Mele, Daniela; Caprio, Francesca; Andreoli, Giada; Vastarella, Maria Giovanna; de Franciscis, Pasquale; Ronsini, Carlo (Frontiers in Cell and Developmental Biology, 2024)
Background: Ovulatory dysfunction is more common in women with obesity. Body fat distribution is also crucial because anovulatory women have a greater waist circumference and more abdominal fat than ovulatory women of similar BMI. The primary aim of the present study is to determine whether there is a relationship between BMI and reproductive characteristics, including hormonal values, antral follicle count (AFC), endometrial assessment at transvaginal ultrasound evaluation (TVUS) during controlled ovarian stimulation (COS), and oocyte retrieval after Ovum Pick-Up (OPU). Methods: Data from a cohort of 183 patients were analyzed and divided into three groups based on weight status: normal weight, overweight, and obesity. Evaluated reproductive characteristics included: age, basal values of follicle-stimulating hormone (FSH), luteinizing hormone (LH), 17-beta-estradiol (E2), thyroid stimulating hormone (TSH), anti-müllerian hormone (AMH), antral-follicle-count (AFC), duration of COS, E2, and progesterone at the last monitoring, TVUS endometrial thickness at the last monitoring before OPU, FOI after OPU. Additionally, the number of meiosis II oocytes retrieved (MII), the total dose of FSH administered, the ratio between MII and total FSH administered, and OSI were registered. Results: AMH levels were significantly lower in obese patients compared to normal weight and overweight women (1. 05 IQR 1.20, 1.58 IQR 2.16, 1.32 IQR 1.38, respectively,. When looking at the MII/FSH ratio, the normal weight group showed a median value of 3.3 with an IQR of 4.0, the overweight group showed a median value of 2.3 with an IQR of 1.9, and the obese group had a median value of 2.6 with an IQR of 2.8. Those data were statistically significant (p-value = 0.049). Conclusions: These results emphasize the importance of considering weight status in fertility assessment and treatment planning.